What's in a Name? From Social Organization to Merit Society: Understanding the Change in Buddhist Charities in China Since the Beginning of the Reform Period - Jiang, Yuxuan (Université d'Ottawa / University of Ottawa, 2018)
After the Chinese Communist Party (CCP) abolished its total ban on religious activities in 1982, a Buddhist revival has taken place in the People’s Republic of China (PRC). Decades later, after the state gradually opened the public welfare sector to non-state actors, Buddhist charities have grown into important social service providers in the country. However, Buddhist charities do not constitute a homogenous category, nor is the emergence of Buddhist charities without direction and monitoring by the Chinese state. This thesis answers the question of why there are different types of Buddhist charities, namely Buddhist merit societies, Buddhist charity foundations and Buddhist charity federations by examining the PRC’s institutions of religions, social organizations and charitable NGOs in the past decades. I have divided the timeline since 1982 into three major time periods and examine the interaction between various levels of government and Buddhist charities. This thesis has demonstrated that the existence of different types of Buddhist charities is the result of inconsistency and fragmentation of these interactions. While the central-led institutionalization of social organizations is creating more obstacles for Buddhist charities to survive, local governments have more interest in their usefulness to the local development. The reason to the question that why Buddhist charities have different identities such as Buddhist merit society, Buddhist charity foundation and Buddhist charity federation has a close link to whether Buddhist groups or sites have sufficient financial resources and well-established government connections.
Keywords: Buddhist charity; China